School Leadership Retention: Designing a Bioecological Model for Leadership Retention; [la Retención de la Dirección Escolar. Diseño de Un Modelo Bioecológico Sobre la Retención Directiva] - Dinamarca-Varas, P; Galdames-Poblete, S (Universidad Autonoma de Madrid, 2025)
Previous research has highlighted the fundamental contribution of leadership in school improvement. Principals are key in mobilizing school transformation processes, fostering teacher capacities and motivations, and setting optimal organizational conditions to support teaching and learning. Previous studies have pointed out the importance of principal retention for the success of school improvement processes. The purpose of this article is to contribute to the area of talent management by proposing a model that could help explain and reduce principal attrition. Using the integrative literature review strategy, we have explored the last two decades (2001-2021) of publications on management retention. A total of 28 articles were analysed in depth, identifying 23 central variables that could explain the management decision to stay or withdraw from school. We organize these variables in a bioecological model, including individual, interpersonal, organizational, community, and political dimensions. The results are an invitation to public policymakers, educational administrators and educational leaders to generate strategies to strengthen the retention of principals and directors. We conclude by presenting limitations and directions for future research. © 2025 Universidad Autonoma de Madrid. All rights reserved.
Keywords: Education; School; Principals; Leadership; Educational policy